Effectiveness of the numbered heads together strategy in improving motivation towards the English language subject among fifth grade primary school pupils". - Muna Abdul-Hussein Husood / Fatima Raheem Abdul Hhssein ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
This study aims at at findingt the effectiveness of the numbered heads strategy in improving the motivation of fifth- grade primary school pupils in the English language. To achieve the aims of the study, null hypotheses have been put on after being subjected to experiment. The study is restricted fifth- grade primary school of female pupils in the city of Dhi-Qar during the academic year 2023-2024. The sample of the study consists of (58) subjects, (29) pupils represent the experimental group, and (29) pupils represent the control group. The experimental group has been taught by using numbered heads strategy, and the control group has been taught by using "English for Iraq Text book " . The process of equivalence of the two groups has been carried out in the light of the following variables: pupils’ ages, , parents educational attainment, the degree of the pretest tests. The researcher taught the experimental group as well as the control group. There is no a statistically significant difference between the mean scores of the development of the experimental group taught by the numbered heads strategy . According to the findings of this study, the students of the experimental groups who are taught by using the numbered heads strategy have significantly improved in motivation. This has been based on a comparative statistical treatment of the students s subject’s scores on both groups of the pretest and the posttest. The study recommended a number of recommendations and a number of suggestions